THE CONTRIBUTION OF SELF-ESTEEM AND LANGUAGE LEARNING STRATEGIES TO THE STUDENTS’ ENGLISH PROFICIENCY FOR SECOND YEAR STUDENTS OF SMA NEGERI 7 DENPASAR - Pramita, Gusti Ayu Putri (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
Abstract Keywords: self-esteem, language learning strategies, students? English proficiency   This study aimed at finding out whether (1) there is a positive and significant contribution of self-esteem to the students? English proficiency for second year students of SMA Negeri 7 Denpasar, (2) there is positive and significant contribution of language learning strategies to the  students? English proficiency for second year students of SMA Negeri 7 Denpasar, and (3) there is positive and significant contribution of self-esteem and language learning strategies to the students? English proficiency for second year students of SMA Negeri 7 Denpasar. It was conducted in SMA Negeri 7 Denpasar. The data were gained by using two kinds of questionnaires Students? Self-Esteem Questionnaire and Strategy Inventory of Language Learning and TOEFL Prediction Test. This research was a predictive study and was conducted as quantitative research by using ex-post facto research design. The simple regression and multiple regressions were used in analyzing the research. From the result, it was found that (1) there was positive and significant contribution of self-esteem to the students? English proficiency for second year students of SMA Negeri 7 Denpasar with contribution 88.36%, (2) there was positive and significant contribution of language learning strategies to the  students? English proficiency for second year students of SMA Negeri 7 Denpasar with contribution 62.9%, and (3) there was positive and significant contribution of self-esteem and language learning strategies to the students? English proficiency for second year students of SMA 7 Denpasar with contribution 91.01%.   1. Background of the Study